MLL gene rearrangements in infant leukemia vary with age at diagnosis and selected demographic factors: A Children’s Oncology Group (COG) study - Sam, Thien N. (2011)
BACKGROUND: Infant leukemias have a high frequency of mixed lineage leukemia (MLL) gene rearrangements. PROCEDURE: Using data from a large etiologic study, we evaluated the distribution of selected demographic factors among 374 infant leukemia cases by leukemic subtype, MLL status and diagnosis age. RESULTS: Overall, 228 cases were MLL+. Compared to white infants, black infants were significantly less likely to have MLL+ leukemia. Further, there was a statistically significantly higher age at diagnosis for infants with t(9;11) translocations compared to all other translocation partners in both acute lymphoblastic leukemia and acute myeloid leukemia cases. CONCLUSION: These patterns may provide important etiological insight into the biology of infant leukemia.